A Cross-Sectional Study on the Relationship Among Cytokines, 5-HT2A Receptor Polymorphisms, and Sleep Quality of Non-manual Workers in Xinjiang, China - Wang, Juan; Gao, Xiaoyan; Gao, Pengcheng; Liu, Jiwen (Frontiers in Psychiatry, 2022)
Background Studies have shown that cytokine activity changes during the sleep-wake process, suggesting that inflammatory factors may be involved in a mechanism affecting sleep quality. Furthermore, the serotonergic system is also one of the essential components of airway relaxation during sleep, especially the serotonin 2A receptor (5-HTR2A) type that plays an important role in the sleep-wake process. Therefore, this research aimed to investigate the effects of cytokines and 5-HTR2A polymorphisms on sleep quality in non-manual workers in Urumqi, Xinjiang in order to explore the relationship between the three. Methods This study used a cluster sampling method to randomly select non-manual workers who worked in Urumqi, Xinjiang for at least 1 year. From July 2016 and December 2017, this study recruited 1,500 non-manual workers for physical examination in the First Affiliated Hospital of Xinjiang Medical University. According to the inclusion and exclusion criteria, 1,329 non-manual workers were finally included in the questionnaire study. It used the Pittsburgh Sleep Quality Index questionnaire to assess sleep quality. Moreover, another 15% of respondents were randomly selected as the experimental study group. The polymerase chain reaction restriction fragment length polymorphism was used to detect 5-HTR2A gene genotypes. Simultaneously, the cytokine (IL-1β, IL-2, IL-6, and TNF-α) content was evaluated using an enzyme-linked immunoassay. Results The results showed that among the 1,329 respondents, 870 had sleep quality problems, and the detection rate was 65.46%. The distribution of −1438G/A genotypes in the 5-HTR2A gene was significantly different among different sleep quality groups (p < 0.05), with no statistical significance present when comparing to T102C (p > 0.05). Logistic regression analysis showed that the AG [odds ratio (OR) = 2.771, 95% confidence interval (CI): 1.054–7.287] and GG (OR = 4.037, 95% CI: 1.244–13.105) genotypes at −1438G/A loci were both associated with poor sleep quality and were thus considered the susceptibility genotypes for sleep problems. Furthermore, IL-1β was shown to be a protective factor for sleep quality (OR = 0.949, 95% CI: 0.925–0.974). The interaction results showed that AG × IL-1β (OR = 0.952, 95% CI: 0.918–0.987) was associated with a lower risk of sleep problems than AA × IL-1β. Conclusion Cytokines and 5-HTR2A polymorphisms not only have independent effects on sleep but also may have cumulative effects. Therefore, it is necessary to further explore the related mechanisms affecting sleep quality to improve the sleep quality of non-manual workers.